Long Segment Left Anterior Descending Endarterectomy [10 cm] and its Reconstruction Using Left Internal Thoracic Artery - Nagre, Suraj Wasudeo (Journal of Cardiovascular Medicine and Cardiology, 2016)
Although coronary endarterectomy is an option for surgical reconstruction of a diffusely diseased vessel, it has not been widely used. In coronary artery bypass grafting, a diffusely diseased left anterior descending coronary artery (LAD) is an obstacle to achieving complete revascularization, consequently leading to the possibility of a poor prognosis. Here, we report a successful case of long segmental reconstruction of a diffusely diseased LAD using a left internal thoracic artery onlay patch after endarterectomy and its early clinical and angiographic assessment.